Pengaruh Pelatihan Kerja, Kemampuan Kerja, dan Stres Kerja Terhadap Kinerja Karyawan Pada PT. Waskita Karya (Persero) Tbk. Proyek Pembangunan Jalan Tol Pasuruan – Probolinggo Seksi 4 - Anggun Rizki Syafila Putri; Pardiman Pardiman; Sulton Sholehuddin (E-JRM : Elektronik Jurnal Riset Manajemen, 2023)
Abtract In a corporate environment or business field, labor is one of the most valuable resources and plays a major role in the use of other company resources. So it is only natural that the company thinks about how to improve the performance of its employees so that the company’s productivity can increase. The purpose of this study was to determine the effect of job training, work ability and work stress on employee performance. The type of research used is associative research with a quantitative approach. The sample in this study were 56 employees who were employees working at PT. Waskita Karya (Persero) Tbk. Pasuruan – Probolinggo Toll Road Construction Project Section 4 . Data analysis used in this study is multiple linear regression analysis. The sample technique used is purposive sampling technique. The results of this study indicate that the independent variables of job training, work ability, and work stress have a partial effect on employee performance. While the results of the F test state that the independent variables simultaneously affect the dependent variable, namely employee performance. Of the three independent variables that have the most dominant influence on employee performance is work ability because it has the greatest value of the beta coefficient and t count. Keywords: Job Training, Work Ability, Work Stress, Employee Performance